PELATIHAN, PEMBIMBINGAN PTK DAN PUBLIKASI ILMIAH GURU-GURU SMA NEGERI 7 PEKANBARU - Rahmiwati Hilma; Prasetya Prasetya; Hasmalina Nasution; Rahmadini Syafri; Fitra Perdana; Jufrizal Syahri; Sri Hilma Siregar (LPPM UMRI, 2019)
Scientific writing training was one of the efforts to develop the profession of high school teachers N 7 Pekanbaru. The training aims to equip high school teachers of N 7 Pekanbaru in terms of strategizing the scientific papers correctly according to the writing guidelines, and equip the teachers in the scientific writing publication procedures in the journal. The training method is the percentage of resources, discussion and simulation of papers that have been prepared by the trainees. The lecture method is necessary to explain the procedures of scientific writing, including how to arrange class action research into a scientific work. The exercise/practice method is required to give participants a scientific writing for the journal article. This scientific writing training activity in its entirety can be said to be seen from the achievement of the target participants, the achievement of training objectives, the achievement of planned target material, and the ability of participants in Material. The supporting factors in this community service activities are the availability of experts who are imported to the training in SMA N 7 Pekanbaru, participant enthusiasm, the support of the school principal, and the supporting fund of the university . The Output of this activity is expected to have several teacher papers (participants) in the form of journals and proceeding that are ready to be submitted to the relevant journal. Keywords: scientific writings, scientific publications, teacher profession development